Advances in Computing and Communications First International Conference, ACC 2011, Kochi, India, July 22-24, 2011. Proceedings, Part II - Abraham, Ajith; Lloret Mauri, Jaime; Buford, John F.; Suzuki, Junichi; Thampi, Sabu M.; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This volume is the second part of a four-volume set (CCIS 190, CCIS 191, CCIS 192, CCIS 193), which constitutes the refereed proceedings of the First International Conference on Computing and Communications, ACC 2011, held in Kochi, India, in July 2011. The 72 revised full papers presented in this volume were carefully reviewed and selected from a large number of submissions. The papers are organized in topical sections on database and information systems; distributed software development; human computer interaction and interface; ICT; internet and Web computing; mobile computing; multi agent systems; multimedia and video systems; parallel and distributed algorithms; security, trust and privacy.
Electronic reproduction.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer software; Information storage and retrieval systems; Information systems; Artificial intelligence; Electronic books